2016
DOI: 10.3390/ijms18010006
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells and Labeling for Spinal Cord Injury

Abstract: Spinal cord injury (SCI) is a devastating condition that usually results in sudden and long-lasting locomotor and sensory neuron degeneration below the lesion site. During the last two decades, the search for new therapies has been revolutionized with the improved knowledge of stem cell (SC) biology. SCs therapy offers several attractive strategies for spinal cord repair. The transplantation of SCs promotes remyelination, neurite outgrowth and axonal elongation, and activates resident or transplanted progenito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 64 publications
0
11
0
1
Order By: Relevance
“…4,5 Specifically, human induced pluripotent stem cells (hiPSCs) reprogrammed from somatic cells have been recently recognized as a promising cell source for personalized therapies by using the patient's autologous cells. 6,7 Moreover, hiPSCs have been successfully differentiated into neural progenitor cells (NPCs) and then various CNS related cell phenotypes including neurons and glial cells, which are significantly invaluable for in vitro disease modeling, drug discovery, and developing regenerative therapies. 8,9 However, the inferior survival rate of grafted cells and inappropriate cell scaffold platform limit the efficacy of hiPSC-based regenerative therapies.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Specifically, human induced pluripotent stem cells (hiPSCs) reprogrammed from somatic cells have been recently recognized as a promising cell source for personalized therapies by using the patient's autologous cells. 6,7 Moreover, hiPSCs have been successfully differentiated into neural progenitor cells (NPCs) and then various CNS related cell phenotypes including neurons and glial cells, which are significantly invaluable for in vitro disease modeling, drug discovery, and developing regenerative therapies. 8,9 However, the inferior survival rate of grafted cells and inappropriate cell scaffold platform limit the efficacy of hiPSC-based regenerative therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies have already shown the efficiency of the combination of cell therapy and pharmacological approaches [ 14 ]. Transplantation of neural stem/progenitor cells (NSPCs) has shown promising results in the repair and regeneration of lost neural tissues and the associated restoration of neurological deficits [ 14 , 15 , 16 ]. NSPCs include multipotent stem cells present in the periventricular subependymal layer and the subgranular zone of the dentate gyrus in the brain, as well as in the ependymal regions lining the central canal of the spinal cord (epSPCs) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, most of the studies showed that BMSCs transplanted alone could improve the locomotor function following spinal cord injury [18,19,21]. Previous studies have demonstrated that BMSCs could secret neurotrophins to improve the axonal regeneration, such as BDNF, NT-3 [20].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, stem cells that are capable of contributing trophic support or integrating into functional synaptic networks with host tissues are being developed for therapeutic use after SCI [20,21]. Bone marrow stromal cells (BMSCs) are considered as a kind of clinical applaction stem cells for autologous transplantation and no ethical issue [22].…”
Section: Introductionmentioning
confidence: 99%